Implementasi Program Sistem Informasi Pelayanan Terpadu Kependudukan Kota Pekanbaru - Yuza, Ahmad Fitra; Febrian, Ranggi Ade; Nurman, Nurman; Purnama, Muhammad Rio (UIR Press, 2025)
SIPENDUDUK is applied to make it easier for the community to obtain administrative public services and is used to apply for the preparation of population documents and civil registration. The purpose of this study is to identify the Implementation of the Pekanbaru City Population Integrated Service System Program. The research method uses a qualitative approach, data collection techniques are observation, interviews, and documentation. The results of this study use George C. Edward III's policy implementation theory which consists of 1) Communication: program implementation can run effectively if the size and goals of the policy are understood by the individuals responsible for achieving the policy objectives, by socializing the program, coordinating between agencies and feedback. 2) Resources, measuring how effective the use of resources is to support the implementation of the SIPOPULATION program which includes human resources, budget and technology. 3) Disposition, refers to the attitude and commitment of policy implementers consisting of work motivation and training quality. 4) The bureaucratic structure consists of service procedures, duties and authorities as well as supervision and evaluation.